Modified polycaprolactone scaffold as well as preparation method and application thereof

By combining nanoclay modifier with hydroxyapatite and polycaprolactone, the mechanical properties and biological activity problems of 3D-printed polycaprolactone-based bone tissue engineering scaffolds are solved, bone regeneration and immune regulation are achieved, suitable for bone defect repair, and are suitable for 3D printing and molding. The raw materials are easy to obtain and cost controllable.

CN120478721APending Publication Date: 2025-08-15遵义医科大学第二附属医院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510628290.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

The existing 3D printed polycaprolactone-based bone tissue engineering scaffolds have slow degradation speed, poor mechanical properties, low cell affinity, and it is difficult to achieve uniform dispersion of inorganic particles, promote bone regeneration and immune regulation, and the preparation process is complex and difficult to industrialize.

Method used

Nanoclay is used as a modifier and is combined with hydroxyapatite and polycaprolactone to prepare a modified polycaprolactone scaffold through a step-by-step composite process. The layered structure and surface characteristics of the nanoclay are used to enhance mechanical properties, promote cell adhesion and osteogenesis differentiation, and regulate the immune microenvironment.

Benefits of technology

The coordinated optimization of mechanical properties, biological activity and immune regulation is achieved. The scaffold has compressive strength close to cancellous bone, promotes cell migration and bone regeneration, is suitable for bone defect repair, is suitable for 3D printing and molding, and the raw materials are easy to obtain and cost controllable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005404564590000011
    Figure HDA0005404564590000011
  • Figure HDA0005404564590000012
    Figure HDA0005404564590000012
  • Figure HDA0005404564590000021
    Figure HDA0005404564590000021
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, and discloses a modified polycaprolactone stent as well as a preparation method and application thereof. The modified polycaprolactone scaffold is prepared from the following raw materials: polycaprolactone, hydroxyapatite, nano clay and a solvent, wherein the nano clay is selected from at least one of montmorillonite, layered double hydroxides, attapulgite, sepiolite, kaolin and synthetic nano clay. According to the modified polycaprolactone scaffold provided by the invention, based on the synergistic effect of hydroxyapatite and nano-clay, collaborative optimization of mechanical properties, biological activity and an immune regulation function is realized, the scaffold has compressive strength close to that of cancellous bone, cell adhesion and migration are remarkably promoted through a hierarchical porous structure and a hydrophilic surface, and the scaffold has a good application prospect. The synergistic effect of the hydroxyapatite and the nano-clay not only induces osteogenic differentiation of stem cells, but also regulates and controls the macrophages to promote repair M2 type polarization, and creates a microenvironment beneficial to bone regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a modified polycaprolactone stent and a preparation method and application thereof. Background Art

[0002] 3D printing creates three-dimensional objects by depositing layers of raw materials on a flat surface. It has been widely used due to its unique advantages, including high precision, customizable manufacturing, and ability to construct complex shapes. Currently, the more mature 3D printing technologies include photopolymerization 3D printing, fused deposition modeling 3D printing, inkjet 3D printing, and laser sintering 3D printing. The basic principle of fused deposition modeling is that the base material is heated in a nozzle to a temperature slightly above its melting point. Under pressure, the base material is extruded from the nozzle into filaments. The nozzle is then moved three-dimensionally under computer control, thereby forming the base material filaments.

[0003] An ideal bone tissue engineering scaffold should possess an interconnected porous network structure, providing interconnected pathways for cell migration, ion transport, and cell-to-cell interactions. To address diverse locations, injury scenarios, and individual differences, the preparation of bone tissue engineering scaffolds requires customization capabilities. Conventional bone tissue engineering scaffold preparation methods, such as foaming, sacrificial templates, freeze-drying, and casting, no longer meet these requirements. In contrast, 3D printing technology allows for the free design of scaffold porosity and shape, better meeting the needs of bone tissue engineering.

[0004] Recent research in osteoimmunology indicates that the complex interactions between biomaterials and host cells are crucial for the fate of implanted biomaterials. Following implantation of a bioscaffold, changes in the body's immune microenvironment play a crucial role in osteogenesis. However, an excessively inflammatory microenvironment can lead to complications such as delayed bone healing, poor osseointegration, and implant failure. Exploring and designing scaffold materials that can modulate macrophage polarization holds promise for enhancing the bone repair effects of biomaterials.

[0005] As a typical synthetic polymer, polycaprolactone is widely used in the biomedical field due to its excellent biocompatibility and degradability. However, polycaprolactone-based scaffolds have problems such as slow degradation, poor mechanical properties, and low cell affinity, which greatly limit their application in tissue engineering. The existing technology modifies polycaprolactone scaffolds by adding hydroxyapatite. Hydroxyapatite is the main inorganic component in bone and has good biocompatibility. Previous studies have shown that polycaprolactone composite scaffolds modified with hydroxyapatite exhibit good biological activity in bone repair. However, the osteoinductive activity of this composite system still fails to meet the biological requirements for ideal bone regeneration. Although the osteoinductive activity of the scaffold can be improved with the increase of hydroxyapatite content, the brittleness of the material is also significantly enhanced. Therefore, hydroxyapatite / polycaprolactone composite scaffolds with a higher hydroxyapatite content are not suitable as bone repair scaffolds.

[0006] In addition, existing 3D printed polycaprolactone-based scaffolds generally have problems such as uneven dispersion of inorganic particles, difficulty in simultaneously achieving the effects of promoting bone regeneration and immune regulation, complex preparation processes, and difficulty in industrialization. Summary of the Invention

[0007] The present invention aims to solve at least one of the above-mentioned technical problems in the prior art. To this end, one of the purposes of the present invention is to provide a modified polycaprolactone stent.

[0008] A second object of the present invention is to provide a method for preparing the modified polycaprolactone scaffold.

[0009] The third object of the present invention is to provide applications of the modified polycaprolactone stent.

[0010] In order to achieve the above object, the technical solution adopted by the present invention is:

[0011] The first aspect of the present invention provides a modified polycaprolactone scaffold, which is prepared from the following raw materials: polycaprolactone, hydroxyapatite, nanoclay and solvent; wherein the nanoclay is selected from at least one of montmorillonite, layered double hydroxide, attapulgite, sepiolite, kaolin and synthetic nanoclay.

[0012] In some embodiments of the present invention, the molecular weight of the polycaprolactone is 30,000-60,000 Da.

[0013] In some embodiments of the present invention, the hydroxyapatite is synthetic hydroxyapatite; the synthesis methods include wet precipitation, hydrothermal synthesis and sol-gel method.

[0014] In the present invention, synthetic hydroxyapatite is used. Natural hydroxyapatite (such as animal bone extract) usually has high crystallinity and stable structure, but low biological activity; while synthetic hydroxyapatite can be controlled to have low crystallinity or amorphous structure through wet precipitation, hydrothermal synthesis and other methods, and is more likely to release calcium and phosphorus ions, thereby promoting cell adhesion and osteogenic differentiation.

[0015] In some embodiments of the present invention, the solvent is selected from at least one of dichloromethane, chloroform, tetrahydrofuran, and ethyl acetate.

[0016] In some embodiments of the present invention, the mass ratio of polycaprolactone to hydroxyapatite is 1:(0.05-0.3).

[0017] In some preferred embodiments of the present invention, the mass ratio of the polycaprolactone to hydroxyapatite is 1:(0.05-0.25).

[0018] The basic principles of the present invention are described as follows:

[0019] The present invention uses nanoclay as a modifier, and its modification effect is specifically reflected in:

[0020] 1) Enhanced mechanical properties: ① Layered structure enhancement: Nanoclay has a layered silicate structure, and its layers can be evenly dispersed in the polycaprolactone matrix to form a "nanocomposite" structure. Through physical cross-linking, the compressive strength and elastic modulus of the scaffold are improved. ② Interface bonding optimization: The surface hydroxyl groups (-OH) of the nanoclay form hydrogen bonds with the ester bonds (-COO-) of polycaprolactone, reducing inorganic-organic phase separation and avoiding brittle fracture.

[0021] 2) Bioactivity regulation: ① Promote osteogenic differentiation: Silicon and magnesium ions released by nanoclay can activate osteogenic-related genes (such as ALP and RUNX2), accelerating bone regeneration; ② Improve cell affinity: The hydrophilic surface of nanoclay can improve the hydrophobicity of the polycaprolactone matrix and promote cell adhesion;

[0022] 3) Immune microenvironment regulation: Nanoclay induces macrophage polarization toward the pro-repair M2 type through surface charge or ion release, inhibits inflammatory response, and thus creates a microenvironment conducive to bone regeneration.

[0023] The second aspect of the present invention provides a method for preparing the modified polycaprolactone scaffold described in the first aspect of the present invention, comprising the following steps:

[0024] S1, dissolving polycaprolactone in a solvent, adding hydroxyapatite to obtain a hydroxyapatite / polycaprolactone solution, and drying to obtain a hydroxyapatite / polycaprolactone film;

[0025] S2. mixing the hydroxyapatite / polycaprolactone film with nanoclay and a solvent to obtain a hydroxyapatite / nanoclay / polycaprolactone solution, and heat-treating the solution to obtain a hydroxyapatite / nanoclay / polycaprolactone block;

[0026] S3. Place the hydroxyapatite / nanoclay / polycaprolactone block into a 3D printing barrel and print layer by layer to obtain the modified polycaprolactone scaffold.

[0027] In some embodiments of the present invention, in step S1, the solid-to-liquid ratio of the polycaprolactone to the solvent is 1 g:(5-25) mL.

[0028] In some preferred embodiments of the present invention, in step S1, the solid-to-liquid ratio of the polycaprolactone to the solvent is 1 g:(5-20) mL.

[0029] In some embodiments of the present invention, in step S1, the solution is stirred after the hydroxyapatite is added; the stirring speed is 200-800 rpm, and the time is 20-100 h.

[0030] In some embodiments of the present invention, in step S1, the drying temperature is 20-30° C. and the drying time is 20-40 h.

[0031] In some preferred embodiments of the present invention, in step S1, the drying temperature is 20-25° C. and the drying time is 20-30 h.

[0032] In some embodiments of the present invention, in step S1, the drying specifically comprises the following steps: placing the hydroxyapatite / polycaprolactone solution in a container, controlling the height of the solution to be less than 2 mm, and air-drying.

[0033] In some embodiments of the present invention, in step S2, the thickness of the hydroxyapatite / polycaprolactone film is less than 2 mm and the area is less than 10 mm. 2 .

[0034] In some embodiments of the present invention, in step S2, before the mixing, the hydroxyapatite / polycaprolactone film is physically broken to make the block area less than 10 mm. 2 operation.

[0035] In some embodiments of the present invention, in step S2, the ratio of the hydroxyapatite / polycaprolactone film, nanoclay and solvent is (0.5-2.0) g: (0.05-0.2) g: 10 mL.

[0036] In some preferred embodiments of the present invention, in step S2, the ratio of the hydroxyapatite / polycaprolactone film, nanoclay and solvent is (0.5-1.5) g: (0.05-0.15) g: 10 mL.

[0037] In some embodiments of the present invention, in step S2, the heat treatment temperature is 50-100° C. and the time is 5-25 hours.

[0038] In some preferred embodiments of the present invention, in step S2, the heat treatment temperature is 60-80°C and the time is 8-21 hours.

[0039] In some embodiments of the present invention, in step S3, the printing parameters include at least one of the following parameters:

[0040] 1) The needle diameter is 0.2-0.5mm;

[0041] 2) The barrel temperature is 60-100°C;

[0042] 3) The needle temperature is 70-110°C;

[0043] 4) Fiber spacing is (0.7-0.9) mm × (0.7-0.9) mm;

[0044] 5) Printing speed is 5-15mm / s;

[0045] 6) The fiber orientation is 0°-90°;

[0046] 7) Air pressure is 350-450kPa;

[0047] 8) The support layer height is 0.2-0.4mm.

[0048] In some preferred embodiments of the present invention, in step S3, the printing parameters include at least one of the following parameters:

[0049] 1) The needle diameter is 0.25-0.45mm;

[0050] 2) The barrel temperature is 60-95°C;

[0051] 3) The needle temperature is 75-105°C;

[0052] 4) Fiber spacing is (0.7-0.8) mm × (0.7-0.8) mm;

[0053] 5) Printing speed is 5-12mm / s;

[0054] 6) The fiber orientation is 0°-90°;

[0055] 7) Air pressure is 380-450kPa;

[0056] 8) The bracket layer height is 0.2-0.35mm.

[0057] The principle of the preparation method of the present invention is described as follows:

[0058] The traditional method of directly mixing nanoclay and hydroxyapatite easily leads to excessively high solution viscosity, making it difficult to form by 3D printing. The present invention adopts a step-by-step composite process to first prepare a hydroxyapatite / polycaprolactone film and then composite it with nanoclay, which can effectively solve the agglomeration problem caused by direct mixing.

[0059] The third aspect of the present invention provides the use of the modified polycaprolactone scaffold described in the first aspect of the present invention in the preparation of bone tissue repair and regeneration products.

[0060] Compared with the prior art, the present invention has the following beneficial effects:

[0061] 1) The modified polycaprolactone scaffold provided by the present invention achieves synergistic optimization of mechanical properties, bioactivity, and immune regulation function based on the synergistic effect of hydroxyapatite and nanoclay. The scaffold has a compressive strength close to that of cancellous bone, and significantly promotes cell adhesion and migration through its multi-level pore structure and hydrophilic surface. The synergistic effect of hydroxyapatite and nanoclay not only induces the osteogenic differentiation of stem cells but also regulates the polarization of macrophages toward the pro-repair M2 type, creating a microenvironment conducive to bone regeneration.

[0062] 2) The preparation method of the modified polycaprolactone scaffold provided by the present invention solves the problem of inorganic particle agglomeration through a step-by-step composite process, is suitable for 3D printing, has readily available raw materials and controllable costs, and has significant clinical application value and industrialization prospects in fields such as bone defect repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 The following are scanning electron microscope images of the stents in Example 1 and Comparative Examples 1-3;

[0064] Figure 2 is the porosity of the scaffolds in Examples 1-3 and Comparative Examples 1-3;

[0065] Figure 3 is the compressive strength of the stents in Examples 1-3 and Comparative Examples 1-3;

[0066] Figure 4 Static images of droplets in the hydrophilicity test of the stent in Example 1 and Comparative Examples 1-3;

[0067] Figure 5 is the contact angle of the stent in Examples 1-3 and Comparative Examples 1-3;

[0068] Figure 6 The results of the cell proliferation promoting performance test of the scaffolds in Example 1 and Comparative Examples 1 and 2 are shown;

[0069] Figure 7 The results of the cell adhesion promoting performance test of the scaffolds in Example 1 and Comparative Examples 1 and 2 are shown;

[0070] Figure 8 The results of MPs polarization gene expression levels of the scaffolds in Example 1 and Comparative Examples 1 and 2 are shown;

[0071] Figure 9 The ALP staining results of the stents in Example 1 and Comparative Examples 1 and 2 are shown;

[0072] Figure 10 The ALP activity test results of the scaffolds in Example 1 and Comparative Examples 1 and 2 are shown;

[0073] Figure 11 These are the osteogenic gene expression results of the scaffolds in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0074] The present invention is further described in detail below using specific examples. Unless otherwise specified, the raw materials, reagents, and apparatus used in the examples and comparative examples are available from conventional commercial sources or by conventional methods. Unless otherwise specified, all experimental or testing methods are conventional in the art.

[0075] Example 1

[0076] In this embodiment, a modified polycaprolactone scaffold is prepared in the following steps:

[0077] S11, dissolving 2 g of polycaprolactone (molecular weight 45000 Da) in 30 mL of dichloromethane, adding 0.3 g of hydroxyapatite (prepared by hydrothermal synthesis), and magnetically stirring at 300 rpm for 24 h to obtain a uniformly dispersed hydroxyapatite / polycaprolactone solution;

[0078] S12. In a fume hood, pour the hydroxyapatite / polycaprolactone solution onto a glass culture dish, controlling the liquid layer height to 1 mm, and place it under ventilation at room temperature for 24 hours to obtain a hydroxyapatite / polycaprolactone film;

[0079] S21. Cut 1.5g of hydroxyapatite / polycaprolactone film into pieces with an area less than 10mm 2 The fragments were dissolved in 10 mL of dichloromethane together with 0.15 g of kaolin nanoclay to obtain a hydroxyapatite / nanoclay / polycaprolactone solution;

[0080] S22, heat-treating the hydroxyapatite / nanoclay / polycaprolactone solution at 80° C. for 8 h to obtain a hydroxyapatite / nanoclay / polycaprolactone block;

[0081] S31. Place the hydroxyapatite / nanoclay / polycaprolactone block into the 3D printing barrel, match it with a 0.25mm diameter needle, set the barrel temperature to 80°C, the needle temperature to 85°C, the fiber spacing to 0.75mm×0.75mm, the printing speed to 11mm / s, the fiber orientation to 0°-90°, the air pressure to 420kPa, the support layer height to 0.2mm, and start printing layer by layer at room temperature to obtain a modified polycaprolactone support.

[0082] Example 2

[0083] In this embodiment, a modified polycaprolactone scaffold is prepared in the following steps:

[0084] S11, dissolving 1 g of polycaprolactone (molecular weight 60,000 Da) in 5 mL of dichloromethane, adding 0.05 g of hydroxyapatite (prepared by a sol-gel method), and magnetically stirring at 800 rpm for 36 h to obtain a uniformly dispersed hydroxyapatite / polycaprolactone solution;

[0085] S12. In a fume hood, pour the hydroxyapatite / polycaprolactone solution onto a glass culture dish, controlling the liquid layer height to 1.8 mm, and place it under ventilation at room temperature for 24 hours to obtain a hydroxyapatite / polycaprolactone film.

[0086] S21, cut 0.7g hydroxyapatite / polycaprolactone film into pieces with an area less than 8mm 2 The fragments were dissolved in 10 mL of dichloromethane together with 0.1 g of montmorillonite nanoclay to obtain a hydroxyapatite / nanoclay / polycaprolactone solution;

[0087] S22, heat-treating the hydroxyapatite / nanoclay / polycaprolactone solution at 70° C. for 15 h to obtain a hydroxyapatite / nanoclay / polycaprolactone block;

[0088] S31. Place the hydroxyapatite / nanoclay / polycaprolactone block into the 3D printing barrel, match it with a 0.45mm diameter needle, set the barrel temperature to 60°C, the needle temperature to 75°C, the fiber spacing to 0.75mm×0.75mm, the printing speed to 12mm / s, the fiber orientation to 0°-90°, the air pressure to 450kPa, the support layer height to 0.3375mm, and start printing layer by layer at room temperature to obtain a modified polycaprolactone support.

[0089] Example 3

[0090] In this embodiment, a modified polycaprolactone scaffold is prepared in the following steps:

[0091] S11, dissolving 1 g of polycaprolactone (molecular weight 30,000 Da) in 20 mL of dichloromethane, adding 0.25 g of hydroxyapatite (prepared by hydrothermal synthesis), and magnetically stirring at 200 rpm for 96 h to obtain a uniformly dispersed hydroxyapatite / polycaprolactone solution;

[0092] S12. In a fume hood, pour the hydroxyapatite / polycaprolactone solution onto a glass culture dish, controlling the liquid layer height to 1.5 mm, and place it under ventilation at room temperature for 24 hours to obtain a hydroxyapatite / polycaprolactone film.

[0093] S21. Cut 1.25g of hydroxyapatite / polycaprolactone film into pieces with an area less than 5mm 2 The fragments were dissolved together with 0.05 g of attapulgite nanoclay in 10 mL of dichloromethane to obtain a hydroxyapatite / nanoclay / polycaprolactone solution;

[0094] S22, heat-treating the hydroxyapatite / nanoclay / polycaprolactone solution at 60° C. for 21 h to obtain a hydroxyapatite / nanoclay / polycaprolactone block;

[0095] S31. Place the hydroxyapatite / nanoclay / polycaprolactone block into the 3D printing barrel, match it with a 0.35mm diameter needle, set the barrel temperature to 95°C, the needle temperature to 105°C, the fiber spacing to 0.75mm×0.75mm, the printing speed to 12mm / s, the fiber orientation to 0°-90°, the air pressure to 380kPa, the support layer height to 0.315mm, and start printing layer by layer at room temperature to obtain a modified polycaprolactone support.

[0096] Comparative Example 1

[0097] In this comparative example, a modified polycaprolactone stent was prepared in the following steps:

[0098] S11, dissolving 2 g of polycaprolactone (molecular weight 45000 Da) in 30 mL of dichloromethane to obtain a polycaprolactone solution;

[0099] S21, adding 0.15 g of kaolin nanoclay to the polycaprolactone solution to obtain a nanoclay / polycaprolactone solution;

[0100] S22, heat-treating the nanoclay / polycaprolactone solution at 80° C. for 8 h to obtain a nanoclay / polycaprolactone block;

[0101] S31. Place the nanoclay / polycaprolactone block into the 3D printing barrel, match it with a 0.25mm diameter needle, set the barrel temperature to 80℃, the needle temperature to 85℃, the fiber spacing to 0.75mm×0.75mm, the printing speed to 11mm / s, the fiber orientation to 0°-90°, the air pressure to 420kPa, the bracket layer height to 0.2mm, and start printing layer by layer at room temperature to obtain a modified polycaprolactone bracket.

[0102] Comparative Example 2

[0103] This comparative example prepares a polycaprolactone stent in the following steps:

[0104] 1.3 g of polycaprolactone (molecular weight 45000 Da) was placed in the 3D printing barrel, matched with a 0.25 mm diameter needle, set the barrel temperature to 80 ° C, the needle temperature to 85 ° C, the fiber spacing to 0.75 mm × 0.75 mm, the printing speed to 11 mm / s, the fiber orientation to 0°-90°, the air pressure to 420 kPa, the bracket layer height to 0.2 mm, and started layer by layer printing on a room temperature platform to obtain a polycaprolactone bracket.

[0105] Comparative Example 3

[0106] This comparative example prepares a polycaprolactone stent in the following steps:

[0107] S11, dissolving 2 g of polycaprolactone (molecular weight 45,000 Da) in 30 mL of dichloromethane, adding 0.3 g of hydroxyapatite (prepared by hydrothermal synthesis) and 0.23 g of kaolin nanoclay, and magnetically stirring at 300 rpm for 24 h to obtain a hydroxyapatite / nanoclay / polycaprolactone solution;

[0108] S12. In a fume hood, pour the hydroxyapatite / nanoclay / polycaprolactone solution onto a glass culture dish, controlling the liquid layer height to 1 mm, and place it under ventilation at room temperature for 24 h to obtain a hydroxyapatite / nanoclay / polycaprolactone film;

[0109] S21. Cut 1.5g of hydroxyapatite / nanoclay / polycaprolactone film into pieces with an area less than 10mm. 2 The fragments were placed in the 3D printing barrel, matched with a 0.25mm diameter needle, and the barrel temperature was set to 80℃, the needle temperature to 85℃, the fiber spacing to 0.75mm×0.75mm, the printing speed to 11mm / s, the fiber orientation to 0°-90°, the air pressure to 420kPa, the bracket layer height to 0.2mm, and layer-by-layer printing was started at room temperature to obtain a modified polycaprolactone bracket.

[0110] Material characterization and performance testing

[0111] 1. The stents prepared in Example 1 and Comparative Examples 1-3 were freeze-dried and gold-sprayed, and then subjected to scanning electron microscopy to observe their surface morphology:

[0112] Figure 1 The scanning electron microscope images of the stents in Example 1 and Comparative Examples 1-3 are shown. Figure 1 It can be seen that the surface of the modified polycaprolactone scaffold prepared in Example 1 is porous and uniform, and the nanoclay and hydroxyapatite particles are well dispersed without agglomeration; the one-step mixing process used in Comparative Example 3 causes the hydroxyapatite and nanoclay to agglomerate into blocks, indicating that the step-by-step composite process provided by the present invention can effectively solve the agglomeration problem caused by direct mixing. In Comparative Example 1, only kaolin nanoclay is added without hydroxyapatite. It can be seen that compared with the pure polycaprolactone scaffold in Comparative Example 2, the number of surface pore structures, pore size and surface roughness are significantly reduced. It is speculated that the nanoclay layer structure forms a physical cross-linked network in the polycaprolactone melt, which significantly increases the melt viscosity of the composite material. During the 3D printing process, the fibers are denser after extrusion of the high viscosity melt, and the interlayer pores are compressed, resulting in a reduction in macroscopic pores; while the surface roughness and pore size of the scaffold in Example 1 are not significantly different from those in Comparative Example 2.

[0113] 2. The porosity of the stents prepared in Examples 1-3 and Comparative Examples 1-3 was tested:

[0114] The mass of the dried scaffold sample was measured and recorded as M0. The pycnometer was filled with anhydrous ethanol at room temperature, and the total mass was recorded as M1. The scaffolds were placed in the pycnometer respectively, and the total mass measured after ultrasonic treatment for 5 minutes to remove all bubbles was recorded as M2. The sample was taken out and the remaining mass was recorded as M3. The porosity calculation formula is: P = (M2-M3-M0) / (M1-M3)*100%.

[0115] Figure 2 is the porosity of the stents in Examples 1-3 and Comparative Examples 1-3, Figure 2 As can be seen, the porosity of the scaffolds in Examples 1-3 and Comparative Examples 1-3 all ranged from 60% to 70%, with no significant difference, demonstrating the consistency of the printing parameters. The porosity of the scaffold in Example 1 was higher than that in Comparative Example 3, indicating that the one-step mixing process in Comparative Example 3 caused agglomeration of hydroxyapatite and nanoclay, leading to pore blockage. The porosity of the scaffold in Example 1 was comparable to that of the pure polycaprolactone scaffold in Comparative Example 2, demonstrating that the present invention solves the problem of inorganic particle dispersion while maintaining high porosity.

[0116] 3. Compressive strength test of the stents prepared in Examples 1-3 and Comparative Examples 1-3:

[0117] After the stent is dried, place it in an INSTON testing machine (34sc -5) and the compression speed was set to 1 mm / min, and the bracket was subjected to a compressive strength test.

[0118] Figure 3 is the compressive strength of the brackets in Examples 1-3 and Comparative Examples 1-3, Figure 3 It can be seen that compared with the pure polycaprolactone scaffold in Comparative Example 2, the compressive strength of the modified polycaprolactone scaffold with the addition of nanoclay in Comparative Example 1 is significantly improved, and the compressive strength of the modified polycaprolactone scaffold with the addition of hydroxyapatite and nanoclay in Examples 1-3 is also improved; although the compressive strength of the scaffold in Comparative Example 1 is much higher than that in Examples 1-3, it is also much greater than the compressive strength of human cancellous bone (2-10 MPa) and is not suitable for bone repair. Therefore, the modified polycaprolactone scaffold provided by the present invention is based on the synergistic effect of hydroxyapatite and nanoclay, which increases the compressive strength of the polycaprolactone scaffold to a range suitable for bone repair; and the compressive strength of the scaffold in Examples 1-3 is higher than that of the scaffold prepared by the one-step mixing process in Comparative Example 3, indicating that the method provided by the present invention is more conducive to improving the mechanical properties of the scaffold by improving the dispersion uniformity of inorganic particles.

[0119] 4. Hydrophilicity test of the stents prepared in Examples 1-3 and Comparative Examples 1-3:

[0120] Place the stent to be tested on a lifting platform, adjust the height of the lifting platform, and use a contact angle meter to drop a drop of liquid on the surface of the stent. The amount of liquid dropped each time is 2 μL. Adjust the position where the sample contacts the droplet to coincide with the measurement baseline. Take a picture to obtain a static image of the droplet at this time. Use the contact angle measurement software to calculate the contact angle (θ) of each group of stents.

[0121] Figure 4 The static images of the droplets in the hydrophilicity test of the stent in Example 1 and Comparative Examples 1-3 are shown. Figure 5 is the contact angle of the stent in Examples 1-3 and Comparative Examples 1-3, Figure 5 It can be seen that the pure polycaprolactone scaffold in Comparative Example 2 has strong hydrophobicity and the largest contact angle. The hydrophobicity of the scaffold decreases after the addition of nanoclay in Comparative Example 1. After the scaffolds in Examples 1-3 are further compounded with hydroxyapatite, the contact angle of the scaffold is significantly reduced (p<0.001), and the hydrophilicity is further improved, which is more conducive to promoting cell adhesion.

[0122] 5. The cell proliferation promoting performance of the scaffolds prepared in Example 1 and Comparative Examples 1 and 2 was tested:

[0123] After recovery, rat bone marrow mesenchymal stem cells (BMSCs) were cultured in a constant temperature cell culture incubator at 37°C and 5% CO2 concentration. BMSCs were cultured in DMEM medium containing 10% fetal bovine serum (FBS), 100 μg / mL penicillin, and 100 μg / mL streptomycin. Cells were passaged when the confluence reached 70%-80%. The cell generations used in this experiment were all 3-5 generations. Before the experiment, each group of scaffolds was sterilized by cobalt-60 irradiation, and then the sterilized scaffold samples were placed in a 48-well plate. A blank control group was set up, and 1×10 cells were seeded in each sample. 4 After 1, 3, and 7 days of culture, the culture medium was removed, and the cell proliferation activity on different scaffolds was assessed using a CCK-8 assay, and the OD value was measured using a microplate reader.

[0124] Figure 6 The results of the cell proliferation promoting performance test of the scaffolds in Example 1 and Comparative Examples 1 and 2 are as follows: Figure 6 It can be seen that on the first day of culture, there was no significant difference in the number of proliferating BMSCs cells on each scaffold. After 3 days of culture, the number of proliferating BMSCs cells on the scaffolds in Example 1 and Comparative Example 1 was significantly higher than that in Comparative Example 2 (p<0.01). The number of proliferating BMSCs cells on the scaffold in Example 1 was slightly higher than that in Comparative Example 1, but the difference was not obvious. After 7 days of culture, the number of proliferating BMSCs cells on the scaffold in Example 1 was significantly higher than that in Comparative Example 1 and Comparative Example 2 (p<0.01), indicating that the modified polycaprolactone scaffold, hydroxyapatite and nanoclay provided by the present invention can synergistically promote cell metabolism.

[0125] 6. Test the cell adhesion performance of the scaffolds prepared in Example 1 and Comparative Examples 1 and 2:

[0126] The cell viability of BMSCs was determined by staining the cells on the sample surface with live-dead cell dyes. The morphology and distribution of the cells on the sample surface were observed using an inverted fluorescence microscope. After 72 h of adhesion and proliferation on the sample surface, the selected cells were tested.

[0127] Figure 7 The results of the cell adhesion promoting performance test of the scaffolds in Example 1 and Comparative Examples 1 and 2 are as follows: Figure 7 It can be seen that there is almost no BMSCs attached to the pure polycaprolactone scaffold in Comparative Example 2, while the amount of BMSCs cells adhered to the scaffold in Example 1 is significantly higher than that in Comparative Example 1 and Comparative Example 2, indicating that the modified polycaprolactone scaffold provided by the present invention greatly improves the biocompatibility of the polycaprolactone scaffold based on the synergistic effect of hydroxyapatite and nanoclay.

[0128] 7. The scaffolds prepared in Example 1 and Comparative Examples 1 and 2 were tested for the expression level of macrophage (MPs) polarization-promoting genes:

[0129] RAW264.7 cells were plated at 5 × 10 4 Cells were seeded at a density of 100 cells / mL onto scaffold samples in 48-well plates, with a blank control group set up. On days 1 and 3, the culture medium was removed, and total RNA was extracted from each sample using the column extraction method. After successful RNA extraction, cDNA was obtained by reverse transcription using a PCR top heater. Real-time fluorescence quantitative PCR was used to measure the expression of the M1 immune marker genes tumor necrosis factor α (TNF-α) and recombinant human interleukin-1β (IL-1β), the M2 immune marker gene CD206, and arginase (ARG). Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was used as an internal reference gene.

[0130] Figure 8 The results of MPs polarization gene expression levels of the scaffolds in Example 1 and Comparative Examples 1 and 2 are shown, wherein: Figure 8 (a) shows the expression level of the M1 immune marker gene tumor necrosis factor α. Figure 8 (b) is the expression level of recombinant human interleukin-1β. Figure 8 (c) in the figure shows the expression level of M2 immune marker gene CD206. Figure 8 (d) is the expression level of arginase, Figure 8 It can be seen that compared with the scaffolds in comparative examples 1 and 2, the scaffold in Example 1 significantly upregulated the expression of M2 macrophage-related genes (CD206 and ARG) and inhibited the expression of M1 macrophage-related genes (TNF-α and IL-1β). The specific mechanism of action is: the Mg released by nanoclay 2+ / Si 4+ By regulating the NF-κB signaling pathway, TNF-α expression is inhibited. Its negatively charged surface adsorbs positively charged inflammatory factors (such as IL-1β), reducing their biological activity, thereby inhibiting the expression of M1 macrophage-related genes. The Ca released by hydroxyapatite degradation 2+ The micron-scale rough surface activates the macrophage CaSR receptor and promotes M2 polarization (CD206 upregulation). The physical stimulation provided by the surface guides the macrophage morphology toward the M2 type, thereby upregulating the expression of genes associated with M2 macrophages. These results demonstrate that the modified polycaprolactone scaffold provided by the present invention, based on the synergistic effect of hydroxyapatite and nanoclay, can significantly inhibit M1 inflammatory factors and promote the M2 repair phenotype, demonstrating strong immune regulatory capabilities.

[0131] 8. Evaluation of the in vitro osteogenic performance of the scaffolds prepared in Example 1 and Comparative Examples 1 and 2:

[0132] 1×10 5BMSCs were added to a 48-well plate containing the scaffold sample and a blank well. After 24 hours of culture, the supernatant was aspirated and osteogenic induction medium (100 mL complete medium + 0.39 mg dexamethasone + 1.76 mg vitamin C + 306.11 mg sodium β-glycerophosphate) was added to each well. The medium was changed regularly. On the 7th and 14th days of culture, the medium was aspirated, and the total RNA of the cells was extracted and tested using a microplate reader to calculate its concentration. Subsequently, it was reverse transcribed to obtain cDNA, and the expression of alkaline phosphatase (ALP), runt-related transcription factor 2 (RUNX2), osteopontin (OPN), type I collagen (COLI), and bone morphogenetic protein 2 (BMP-2) was detected by real-time fluorescence quantitative PCR, using GAPDH as an internal reference gene.

[0133] After 7 days of osteogenic induction, scaffolds were stained for ALP using an ALP staining kit, and ALP levels were quantified using an alkaline phosphatase detection kit and the BCA assay. After 14 days of osteogenic induction, scaffolds were stained with Alizarin Red stain, and calcium nodule deposition on the scaffolds was observed under a microscope. After observation, calcium nodules were eluted using a 10% CPC solution, and calcium nodule expression in each sample was quantified using a microplate reader (OD = 562). Table 1 shows the gene primer sequences used in the in vitro osteogenic performance evaluation experiments of the scaffolds.

[0134] Table 1 Gene primer sequences used in the in vitro osteogenic performance evaluation experiment of the scaffold

[0135] Gene name Forward primer sequence (5'-3') Rear primer sequence (5'-3') GAPDH GCCATGAGGTCCACCACCCT AAGGTCATCCCAGAGCTG ALP GGAGATGGTATGGGCGTCTC GGACCTGAGCGTTGGTGTTA RUNX2 TCGGAGAGGTACCAGATGGG AGGTGAAACTCTTGCCTCGT COLⅠ TTCTCCTGGCAAAGACGGAC CTCAAGGTCACGGTCACGAA CD206 ATGGATGTTGATGGCTACTGG TTCTGACTCTGGACACTTGC ARG CATATCTGCCAAAGACATCG CATATCTGCCAAAGACATCG TNF-α GGGTGTTCATCCATTCTC GGTCACTGTCCCAGCAT IL-1β TACAGGCTCCGAGATGAACA AGGCCACAGGTATTTTGTCG

[0136] Figure 9 The ALP staining results of the stents in Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 9 It can be seen that in the staining on the 7th day, the pure polycaprolactone scaffold in Comparative Example 2 did not play a significant role in promoting the osteogenic differentiation of cells, and the ALP staining was less and lighter in color, while the ALP staining in the cells of the Comparative Example 1 scaffold with the addition of nanoclay was significantly increased, and the ALP staining of the Example 1 scaffold with the addition of hydroxyapatite and nanoclay was even more significant.

[0137] Figure 10 The ALP activity test results of the scaffolds in Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 10 It can be seen that the ALP activity of the scaffold of Example 1 is significantly higher than that of Comparative Examples 1 and 2 (p < 0.001).

[0138] Figure 11 The results of osteogenic gene expression of the scaffolds in Example 1 and Comparative Examples 1 and 2 are shown, wherein: Figure 11 (a) is the expression result of alkaline phosphatase. Figure 11(b) in the figure shows the expression results of runt-related transcription factor 2. Figure 11 (c) is the expression result of type I collagen, Figure 11 It can be seen that compared with Comparative Examples 1 and 2, the scaffold in Example 1 showed a significant upregulation of the expression of osteogenesis-related genes on the 7th and 14th days (p < 0.05), indicating that the modified polycaprolactone scaffold provided by the present invention has good osteoinductive activity.

Claims

1. A modified polycaprolactone stent, characterized in that: The invention is prepared from the following raw materials: polycaprolactone, hydroxyapatite, nano clay and solvent; wherein the nano clay is selected from at least one of montmorillonite, layered double hydroxide, attapulgite, sepiolite, kaolin and synthetic nano clay.

2. The modified polycaprolactone stent according to claim 1, characterized in that: The mass ratio of the polycaprolactone to the hydroxyapatite is 1:(0.05-0.3).

3. The method for preparing the modified polycaprolactone stent according to claim 1 or 2, characterized in that: The following steps are involved: S1, dissolving polycaprolactone in a solvent, adding hydroxyapatite to obtain a hydroxyapatite / polycaprolactone solution, and drying to obtain a hydroxyapatite / polycaprolactone film; S2. mixing the hydroxyapatite / polycaprolactone film with nanoclay and a solvent to obtain a hydroxyapatite / nanoclay / polycaprolactone solution, and heat-treating the solution to obtain a hydroxyapatite / nanoclay / polycaprolactone block; S3. Place the hydroxyapatite / nanoclay / polycaprolactone block into a 3D printing barrel and print layer by layer to obtain the modified polycaprolactone scaffold.

4. The preparation method according to claim 3, characterized in that In step S1, the solid-liquid ratio of the polycaprolactone to the solvent is 1 g:(5-25) mL.

5. The preparation method according to claim 3, characterized in that In step S1, the drying temperature is 20-30° C. and the drying time is 20-40 hours.

6. The preparation method according to claim 3, characterized in that In step S2, the thickness of the hydroxyapatite / polycaprolactone film is less than 2 mm and the area is less than 10 mm. 2 .

7. The preparation method according to claim 3, characterized in that In step S2, the ratio of the hydroxyapatite / polycaprolactone film, nanoclay and solvent is (0.5-2.0) g: (0.05-0.2) g: 10 mL.

8. The preparation method according to claim 3, characterized in that In step S2, the heat treatment temperature is 50-100° C. and the time is 5-25 hours.

9. The preparation method according to claim 3, characterized in that In step S3, the printing parameters include at least one of the following parameters: 1) The needle diameter is 0.2-0.5mm; 2) The barrel temperature is 60-100°C; 3) The needle temperature is 70-110°C; 4) Fiber spacing is (0.7-0.9) mm × (0.7-0.9) mm; 5) Printing speed is 5-15mm / s; 6) The fiber orientation is 0°-90°; 7) Air pressure is 350-450kPa; 8) The support layer height is 0.2-0.4mm.

10. Use of the modified polycaprolactone scaffold according to claim 1 or 2 in the preparation of bone tissue repair and regeneration products.